Analysis of production data from the Krafla geothermal field, Iceland - Pruess, K.; Bodvarsson, G. S.; Stefansson, V. (Lawrence Berkeley Laboratory, 1983)
The analysis of flow rate and enthalpy data from several wells completed in the same two-phase zone of Krafla geothermal reservoir has yielded consistent relative permeability parameters. It is found that k/sub rl/ + k/sub rv/ = 1 over the entire range of two-phase flow conditions from immobile liquid to immobile vapor. The available data provide relative permeability parameters as a function of flowing enthalpy only. The relationship between flowing enthalpy and in-place vapor saturation remains unknown, so that the relative permeability information obtained is of limited value for quantitative modeling of geothermal reservoir performance. Numerical simulation of flow rate and enthalpy transients has yielded excellent matches to production data from well 12. However, there is little information about the reservoir which can be deduced in an unambiguous way, because the field data could be matched with a variety of rather different parameter choices. The only unambiguous piece of information obtained is that the water injected into the well during drilling and completion remains in the vicinity of the wellbore during several weeks of warmup.